Secessionist criminals’: an obstruction to the full realisation of the right to self-determination - Madziwa, Edward (Midlands State University, 2019)
A close analysis of some of the countries that have experienced a wave of secessionist movements like Spain, Zambia and Zimbabwe, makes it apparent that there is a criminal penalty visited upon the pioneers of such a movement. Given such developments most leaders of the secessionist groups have been charged with treason, terrorism or rebellion and arraigned before municipal courts. This highlights the inherent difficulties associated with the full exercise of the right to self-determination beyond the decolonisation context. This study undertakes to investigate the full exercise and impact of municipal criminal laws on the right to external self-determination through secession. This study focuses on the secessionist movements in Spain, Zambia and Zimbabwe; the subsequent trials of the leaders of these movements and how these trials impact on the full exercise of the right to self-determination, as provided for in various international and regional treaties and conventions.